1994
DOI: 10.1038/369661a0
|View full text |Cite
|
Sign up to set email alerts
|

Flower colour intensity depends on specialized cell shape controlled by a Myb-related transcription factor

Abstract: Flower colour is determined primarily by the production of pigments, usually anthocyanins or carotenoids, but the shade and intensity of the colour are often changed by other factors such as vacuolar compounds, pH and metal ions. Pigmentation can also be affected by the shape of epidermal cells, especially those facing prospective pollinators. A conical shape is believed to increase the proportion of incident light that enters the epidermal cells, enhancing light absorption by the floral pigments, and thus the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
339
2
12

Year Published

1996
1996
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 420 publications
(365 citation statements)
references
References 19 publications
12
339
2
12
Order By: Relevance
“…This observed prism‐like shape is highly unusual; petal surfaces are most commonly composed of either elongated flat cells or isotropically structured conical‐papillate cells (Kay et al ., 1981; Whitney et al ., 2011; Vignolini et al ., 2012a). The circular or hexagonally based conical‐papillate cells that characterize petals of many other eudicots differ markedly in that the wall is relatively evenly thickened around the entire cell as the conical outgrowth is formed by turgor‐driven expansion of the entire cell and is therefore vacuolated in cross‐section (Noda et al ., 1994). The petal epidermal cells of E. californica apparently represent a unique structure.…”
Section: Discussionmentioning
confidence: 99%
“…This observed prism‐like shape is highly unusual; petal surfaces are most commonly composed of either elongated flat cells or isotropically structured conical‐papillate cells (Kay et al ., 1981; Whitney et al ., 2011; Vignolini et al ., 2012a). The circular or hexagonally based conical‐papillate cells that characterize petals of many other eudicots differ markedly in that the wall is relatively evenly thickened around the entire cell as the conical outgrowth is formed by turgor‐driven expansion of the entire cell and is therefore vacuolated in cross‐section (Noda et al ., 1994). The petal epidermal cells of E. californica apparently represent a unique structure.…”
Section: Discussionmentioning
confidence: 99%
“…An earlier investigation (Noda et al, 1994) of the Mixta+ and mixta-lines of Antirrkinum reported no significant difference in pigmentation between the two, but under our growth and assay conditions we found clear differences in the amount of flavonoid extractable from the two lines (Fig. 4) and tested the significance of differences with Student's t tests on data from each of the wavelengths marked with an error bar.…”
Section: Pigment Contentmentioning
confidence: 62%
“…Although previous studies (Brehm and Krell, 1975;Noda et al, 1994) have implicated epidermal cell shape in influencing absorption of both visible and UV light, this effect has not been quantified. The separate effects of epidermal cell shape and pigmentation have been difficult to identify because these parameters often vary together (Baagae, 1977;Levy, 1978;Rieseberg and Schilling, 1985;Steiner, 1990).…”
mentioning
confidence: 99%
See 2 more Smart Citations